PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI, DAN KONFLIK PERAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada UD. Pandang Laut Desa Banyusangka, Bangkalan Madura) - Umar Faruq; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT       This study aims to examine and analyze the influence of organizational commitment, organiztional culture , and role conflict on the performance of UD. Pandang Laut employees both partially and jointly. The population and sample are all 40 production management employees. Data collection through questionnaires and interviews. Data analysis in this study used SPSS version 16. The sampling technique using census methods and data testing techniques used in this study included validity test, reliability test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis.       The results of the analysis show that partially organizational commitent has a significant positive effect on employee performance while organizational culture, has a positive and insignificant effect on employee performance, and role conflict has a negative effect on employee performance. And together show that Organizational commitment, , Organizational Culture and Role Conflict no significantly influence employee performance. Keywords: Organizational Commitment, Organizational Culture, Role Conflict and Employee Performance.